“Et lille, firfodet Dyr og en Hovedløs mand”: Et præludium over negativitetens æstetik i den tidlige danske middelalder - Melballe Bonde, Line (Periskop – Forum for kunsthistorisk debat, 2023)
This article proposes a new approach to medieval imagery. By taking as a case a relief carving showing a disembodied head, a headless body, a horse and foliage, it argues that this seemingly unintelligible motif can be interpreted based on an approach where the human elements do not dictate the reading alone, as in previous analyses, but that non-human components carry a meaning-driving function as well. The article points out how scholarly approaches to pre-modern imagery, by definition, are culturally conditioned and rooted in the conceptual framework of modernity. It argues that the tendency to understand decapitations and public executions as unilaterally negative cannot be applied to the Middle Ages. Implementing instead a step-by-step shift in the interpretative perspective, the article reaches an understanding of the relief as a representation of a deconstructed anthropomorphic knightly identity where the man and the horse represent the Christian self-sacrificing death, literally and/or morally.